The Pedagogical Significance of Educational Ideas in the Orkhon-Yenisey Inscriptions (Horizon Multidisciplinary Scientific Journal, 2026)
The Orkhon-Yenisei inscriptions, regarded as the earliest examples of written culture among the Turkic peoples, carry profound pedagogical content alongside their well-recognized political and linguistic significance. In this article, the inscriptions are examined through the lens of modern educational science, and the instructive ideas embedded within them are systematically analyzed. The study reveals that the addresses, warnings, and historical examples found in the inscriptions of Bilge Khagan, Kultigin, and Tonyukuk closely align in essence with key concepts in contemporary pedagogy — including values education, the development of critical thinking, leadership training, and the cultivation of historical consciousness. The relationship that state leaders built with their people can further be characterized as an early form of non-formal public enlightenment. Taken together, these features demonstrate that the inscriptions are not merely historical monuments, but a pedagogical legacy passed down from generation to generation.
Keywords: Orkhon-Yenisei inscriptions; pedagogical significance; educational ideas; national consciousness; historical memory